Dupont Analysis for Selected Five Nifty Fifty Companies - Parulekar, Pushkar Dilip (SFIMAR Research Review, 2015)
Equity Shareholders are the residual stakeholders in a company. One of the ways by which objective of financial management is defined is "To maximize the wealth of Equity Shareholders continuously". ROE indicates returns earned by equity shareholders on their investment. DuPont Corporation in the ? 920's created an analysis method. This analysis method breaks up ROE into three very important components. These three components were Operating efficiency. Asset use efficiency and financial leverage. This paper will focus on ROE broken up into these three components using Net Profit Margin (how much profit the company gets out of its revenues), Asset Turnover Ratio (how effectively the company makes use of its assets) and Equity Multiplier (a measure of how much the company is leveraged). Net profit margin will be an indicator towards Operating efficiency. Asset Turnover Ratio would be an indicator towards Asset use efficiency and Equity Multiplier would be an indicator towards financial leverage. Five different companies from five different sectors are being considered viz. Infosys Limited, hindustan Unilever Limited, Larsen & Toubro Limited, Mahindra and Mahindra Limited and Sun Pharmaceutical Industries Limited. These companies represent various sectors in the economy viz. Information Technology (IT), Fast Moving Consumer Goods (FMCG), Capital goods (CG), Automobiles (Auto) and Pharmaceuticals (Pharma). Statistical tools such as Multiple Regression Analysis, ANOVA with 95% confidence are used to infer the results. Data is taken from audited balance sheets and profit and loss accounts for the period from 2005 to 2014.